2022
DOI: 10.3390/cells11111755
|View full text |Cite
|
Sign up to set email alerts
|

Shiga Toxin 2 Triggers C3a-Dependent Glomerular and Tubular Injury through Mitochondrial Dysfunction in Hemolytic Uremic Syndrome

Abstract: Shiga toxin (Stx)-producing Escherichia coli is the predominant offending agent of post-diarrheal hemolytic uremic syndrome (HUS), a rare disorder of microvascular thrombosis and acute kidney injury possibly leading to long-term renal sequelae. We previously showed that C3a has a critical role in the development of glomerular damage in experimental HUS. Based on the evidence that activation of C3a/C3a receptor (C3aR) signaling induces mitochondrial dysregulation and cell injury, here we investigated whether C3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…For lung ultrastructural analysis, glutaraldehyde-fixed fragments of lung tissue were processed and examined with a Philips Morgagni 268D transmission electron microscope (Philips, Brno, Czech Republic), as we previously described 54 , 55 .…”
Section: Methodsmentioning
confidence: 99%
“…For lung ultrastructural analysis, glutaraldehyde-fixed fragments of lung tissue were processed and examined with a Philips Morgagni 268D transmission electron microscope (Philips, Brno, Czech Republic), as we previously described 54 , 55 .…”
Section: Methodsmentioning
confidence: 99%
“…[25][26][27] In vitro studies have revealed that interactions between C3a and C3aR foster an increase in interleukin (IL)-1β production, which subsequently induces podocyte cytoskeletal rearrangements, while inhibition of C3aR mitigates renal injury. 26,28 This structural and functional sophistication underscores the critical role of podocytes in maintaining the delicate balance of glomerular homeostasis.…”
Section: Podocytes As Immune Components In the Kidneymentioning
confidence: 99%
“…Expression of complement factors, including C1q, C2, C3, C7, and protein S, along with complement receptors, C3aR and C5aR, and complement regulators, such as complement factor H and decay‐accelerating factor, underline the role of podocytes in complement activation 25–27 . In vitro studies have revealed that interactions between C3a and C3aR foster an increase in interleukin (IL)‐1β production, which subsequently induces podocyte cytoskeletal rearrangements, while inhibition of C3aR mitigates renal injury 26,28 . This structural and functional sophistication underscores the critical role of podocytes in maintaining the delicate balance of glomerular homeostasis.…”
Section: Podocyte Function In Kidney Physiologymentioning
confidence: 99%